Paradigm Shift in EFL Teacher Education: Multimodality in Grammar-Based Microteaching Practices via Reflections on Lesson Plans - Orak, Suheyla Demirkol (My University, 2025)
In the evolving landscape of language education, integrating 21st-century pedagogical principles such as multimodality, digital literacy, and learner-centered instruction has become imperative. This study explores how pre-service English language teachers reflect these principles in grammar-based microteaching practices, focusing specifically on their lesson plans and instructor observation notes. The primary aim is to investigate the extent to which multimodal approaches and contemporary teaching strategies are embedded in the instructional design and delivery of future educators. Employing a mixed-method sequential research design, the study analyzes scale, reflection notes, and observation feedback from a cohort of 61 teacher candidates. Thematic coding and frequency analysis were used to identify patterns in instructional design, technology integration, group interaction, material development, and classroom management. The findings reveal a significant variance in the incorporation of multimodal tools and communicative strategies, with strong material use and lesson planning but limited production activities and interaction. The results underscore the importance of structured reflection and rubric-based feedback in enhancing pedagogical awareness. Overall, this research contributes to the field of teacher education by highlighting the potential of microteaching as a reflective and developmental tool for promoting innovative, multimodal, and contextually relevant language instruction.
Keywords: Teacher education; EFL; multimodality; microteaching practices; 21st-century teaching principles.